Legal Analysis of the Effectiveness of Waste Management Law in Indonesia Using the Ottawa Charter Health Promotion Framework - Prasetyo, Riris; Narutomo, Teguh (Dinasti Research, 2025)
This study aims to evaluate the effectiveness of the implementation of Law No. 18 of 2008 concerning Waste Management, especially in internalizing the obligation to sort waste from source, by adopting a transdisciplinary approach through the integration of the Ottawa Charter paradigm. Using normative legal research methods, this study examines the applicable positive legal framework and reconstructs its effectiveness based on the five main pillars of the Ottawa Charter. The results of the study indicate that although normatively the waste management policy has reflected the Build Healthy Public Policy principle, its implementation has not been optimal due to weak infrastructure support (Create Supportive Environments pillar) and low community participation (Strengthen Community Action). This inequality creates a legal paradox in which the state demands citizens' obligations without providing adequate support for their fulfillment. The main contribution of this study lies in the development of an adaptive and participatory waste management legal reform model, by making the law a facilitator of collective behavioral change that is ecologically just through a contextual cross-sectoral approach.